Effects of Contact Pressure and Sliding Speed on the Unlubricated Friction and Wear Properties of Zn-15Al-3Cu-1Si Alloy. Issue 6 (1st November 2016) - Hekimoğlu, Ali P.; Savaşkan, Temel
ABSTRACT: The unlubricated friction and wear properties of Zn-15Al-3Cu-1Si alloy were studied over a range of contact pressure (1–5 MPa) and sliding speed (0.5–2.5 ms −1 ) for a sliding distance of 2, 500 m using a block-on-disc type test machine. It was observed that as the contact pressure increased, the friction coefficient of the alloy decreased but its working temperature, surface roughness, and wear volume increased. Sliding speed had no significant effect on the friction coefficient of the alloy but increased its working temperature, surface roughness, and wear volume. It was also observed that the formation of a hard and brittle surface layer had a great influence on the wear behavior of the experimental alloy. The hardness and thickness of this layer increased with increasing contact pressure and sliding speed. However, contact pressure was found to be much more effective on the hardness of the surface layer of this alloy. Both adhesion and abrasion were observed to be the dominant wear mechanisms for the alloy under the given sliding conditions. The results obtained from the friction and wear tests are discussed in terms of the test conditions and microstructural changes that take place during sliding.